INTERCORRELATION ANALYSIS OF PSYCHOLOGICAL FACTORS AFFECTING AGGRESSIVE BEHAVIOR IN MARTIAL ARTS - Tadjibayeva Shakhista Mamatkulovna, Salomova Hulkar Nasimovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the intercorrelation analysis of the psychological factor affecting aggressive behavior is analyzed in detail. Through correlational analysis of the problem of aggressive behavior in sports activities, the positive and negative relationship between the scales of the methods used for the problem is revealed in detail.